2022
DOI: 10.1002/ejhf.2486
|View full text |Cite
|
Sign up to set email alerts
|

The association of improvement in left ventricular ejection fraction with outcomes in patients with heart failure with reduced ejection fraction: data from CHAMP‐HF

Abstract: Aims We assessed for an association between improvements in left ventricular ejection fraction (LVEF) and future outcomes, including health status, in routine clinical practice. Methods and results CHAMP‐HF was a registry of outpatients with heart failure (HF) and LVEF ≤40%. Enrolled participants completed the Kansas City Cardiomyopathy Questionnaire‐12 (KCCQ‐12) at regular intervals and were followed as part of routine care. We assessed for associations between improvements in LVEF (≥10%) over time and concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Our second study aim represented a novelty, to our knowledge, and it is probably the most important finding of our results. Previous studies have shown that patients with HFimpEF or ‘recovered’ LVEF had a better prognosis 15–23 ; but that was not the objective of the present study. Moreover, QoL was previously associated with outcomes in patients with HF 25–30 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our second study aim represented a novelty, to our knowledge, and it is probably the most important finding of our results. Previous studies have shown that patients with HFimpEF or ‘recovered’ LVEF had a better prognosis 15–23 ; but that was not the objective of the present study. Moreover, QoL was previously associated with outcomes in patients with HF 25–30 .…”
Section: Discussionmentioning
confidence: 86%
“…14 Improvement or recovery in LVEF has been associated with better clinical outcomes, including HF-related hospitalizations and survival. [15][16][17][18][19][20][21][22][23] However, the influence of LVEF improvement (or LVEF recovery) on QoL, although reported in a small number of studies, 6,[22][23][24] has not been completely established. Indeed, it has been widely reported that QoL could predict outcomes in HF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wohlfahrt et al (2022) report HF-related quality-of-life impairment after myocardial infarction. DeVore et al (2022) report the association of improvement in the left ventricular ejection fraction with outcomes in patients with HF with a reduced ejection fraction: data from CHAMP-HF. Butler et al (2022b) report health status improvements with ferric carboxymaltose in HF with reduced ejection fraction and iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…DeVore et al 12 . assessed the association between improvement in left ventricular ejection fraction (LVEF) and health status or clinical events among 2092 patients with chronic HF (median LVEF 30%) included in the CHAMP‐HF (Change the Management of Patients with Heart Failure) registry.…”
Section: Effects Of Treatmentsmentioning
confidence: 99%
“…DeVore et al 12 assessed the association between improvement in left ventricular ejection fraction (LVEF) and health status or clinical events among 2092 patients with chronic HF (median LVEF 30%) included in the CHAMP-HF (Change the Management of Patients with Heart Failure) registry. A ≥10% improvement in LVEF was observed in 33% of patients and was associated with better Kansas City Cardiomyopathy Questionnaire-12 (KCCQ-12) overall summary score and with a reduced risk of subsequent all-cause death or HF hospitalization (adjusted hazard ratio 0.50, 95% confidence interval 0.41-0.61).…”
Section: Changes In Left Ventricular Ejection Fraction and Worsening ...mentioning
confidence: 99%